PERFORMANCE OF MACHINES THRESHER SEEDS JOB’S TEARS (Coix Lacryma-Jobi L.) RUBBER ROLL TYPE - Juliardi .; Rofandi Hartanto; Warji .; Budianto Lanya (The University of Lampung, 2013)
Job’s tears (Coix lacrhryma jobi L.) was a plant that came from South Asia and East Asia. The distribution of this plant was expanded to Southeast Asia, especially Indonesia. In Indonesia, Job’s tears was found in Sumatra, Java and Kalimantan. Its seeds had many benefits as herbs or plant consumption. Threshing process of this plant was still using a traditional way. This research was purposed to design and test the performance of jali thresher machine type rubber roll. This research was conducted in February 2013 to March 2013 in the Laboratory of Agricultural Engineering, Department of Agricultural Engineering, Faculty of Agriculture, University of Lampung. This research procedure included several stages: design, assembly, testing results, and data analysis stage. Observations were made for machine capacity per hour, percentage of threshed seeds, and percentage of good or damaged threshed seeds. This research used 3 cylinder rotational speeds: 50 RPM, 38 RPM and 30 RPM. Results of this research indicated that this machine threshed seeds by 47 kg/ hour. Keywords: Job’s tears, threshing, and Rubber Roll